2014
DOI: 10.15740/has/ijpp/7.2/397-400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different diets on the biological parameters of rice moth, Corcyra cephalonica Stainton

Abstract: The effect of different diets on the biological parameters of rice moth, Corcyra cephalonica Stainton (Lepidoptera: Pyralidae) was studied under laboratory condition during 2010 -2011 in the Department of Entomology, Assam Agricultural University, Jorhat, Assam. Among the six diets tested, rice, wheat and groundnut mixture (5:5:1) was found to be the superior rearing medium that enhanced quicker development period of Corcyra cephalonica, maximum fecundity and maximum fresh body weight of full grown larva for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, female moths emerging from larvae fed on different millet and cowpea mix (5–50%) laid 2.4–2.6 times more eggs than those fed on sole millet. Rajkumari et al (2014) and Ahmad et al (2017) recorded highest fecundity with females of C. cephalonica emerging from larvae fed on mixtures of cereals fortified with chickpea flour. Mehendale et al (2014) reported that a sole sorghum diet produced adults with low fecundity.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, female moths emerging from larvae fed on different millet and cowpea mix (5–50%) laid 2.4–2.6 times more eggs than those fed on sole millet. Rajkumari et al (2014) and Ahmad et al (2017) recorded highest fecundity with females of C. cephalonica emerging from larvae fed on mixtures of cereals fortified with chickpea flour. Mehendale et al (2014) reported that a sole sorghum diet produced adults with low fecundity.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies were conducted with a combination of locally available diet ingredients in an effort to enhance production of C. cephalonica culture in the laboratories. The post-embryonic development ranged from 28 to 30 d. Other studies reported 35–40 d using diets including sorghum, pearl millet, rice, wheat, and groundnut (Shazali 1986, Prakash and Senthilkumar 2005, Rajkumari et al 2014, Wadaskar et al 2015). The differences could be attributed to different experimental conditions (i.e., temperature and humidity), but they included duration from egg to adult emergence, while in this study, duration of eggs was not included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides production constraints, the insect pest problem, improper sanitation and storing methods result in both quantitative and qualitative storage losses in sorghum. In storage, the losses are mainly due to insects, mites and pathogens (Kumar et al 2018). Every year, one-third of the world grain crop is lost during storage; much of this is particularly due to insect attack.…”
Section: Introductionmentioning
confidence: 99%
“…Streptomycin has been commonly used for improving the nutritional quality of artificial diets to mass rearing of model insects including Corcyra cephalonica (Pyrallidae: Lepidoptera), Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae), Spodoptera litura (Lepidoptera: Noctuidae), Spodoptera exigua (Lepidoptera: Noctuidae), Rhynocoris marginatus (Hemiptera: Reduviidae) for various purposes at laboratory condition (Sahayaraj and Balasubramanian, 2016;Nair et al 2018;Arun Kumar et al, 2018;Huynh et al 2019). In the case of struggle with microbial contamination in mass rearing of insects, the right proportion of antibiotic agents in artificial diets should be able to prevent microbial contamination but not exert or have less detrimental effects on host insect (Thakur et al 2016;Nair et al 2018;Huynh et al 2019;.…”
Section: Discussionmentioning
confidence: 99%